The role of transient starch in acclimation to elevated atmospheric CO2 - Sonnewald, Uwe; et al. (Febs Letters, 1998)
Although increased concentrations of CO2 stimulate photosynthesis, this stimulation is often lost during prolonged exposure to elevated carbon dioxide, leading to an attenuation of the potential gain in yield. Under these conditions, a wide variety of species accumulates non-structural carbohydrates in leaves, It has been proposed that starch accumulation directly inhibits photosynthesis, that the rate of sucrose and starch synthesis limits photosynthesis, or that accumulation of sugars triggers changes in gene expression resulting in loser activities of Rubisco and inhibition of photosynthesis. To distinguish these explanations, transgenic plants unable to accumulate transient starch due to leaf mesophyll-specific antisense expression of AGP B were grown at ambient and elevated carbon dioxide. There was a positive correlation between the capacity for starch synthesis and the rate of photosynthesis at elevated CO2 concentrations, showing that the capability to synthesize leaf starch is essential for photosynthesis in elevated carbon dioxide, The results show that in elevated carbon dioxide, photosynthesis is restricted by the rate of end product synthesis, Accumulation of starch is not responsible for inhibition of photosynthesis, Although transgenic plants contained increased levels of hexoses, transcripts of photosynthetic genes were not downregulated and Rubisco activity was not decreased arguing against a role of sugar sensing in acclimation to high CO2, (C) 1998 Federation of European Biochemical Societies.
Keywords: carbon dioxide; photosynthesis; ADP-glucose pyrophosphorylase; antisense; sugar sensing; Solanum tuberosum